Measuring the Concentration of Insurance sector – the Case of Southeastern European Countries - Dimić Maja (Organizacija, 2018)
Background and purpose: The goal of the paper is to determine the level of concentration in the insurance sector in the following eight countries of South and Eastern Europe: Serbia, Croatia, Bosnia and Herzegovina, Montenegro, Former Yugoslav Republic of Macedonia, Romania, Bulgaria and Albania in the period from 2007 to 2012.